Detection and Mitigation of Virus Ransomware - Mohd Husny, Herny Ramadhani; Md Yussof, Mohamad Syafiq; Abdullah, Norhaiza Ya; Wan Ismail, Wan Hazimah (Journal of Computing Technologies and Creative Content, 2020)
In this era of globalization, ransomware is not something strange. It is a necessity to know about the dangers of this ransomware virus. Ransomware is a kind of malware that encrypts files on a victim’s computer and requires payment before restoration. It has become a very serious cyber threat nowadays. The basic idea of ransomware was presented in the form of a cryptovirus in 1995. However, it was considered as merely a conceptual topic since then for over a decade. In 2017, ransomware has become a reality, with several famous cases of ransomware having compromised important computer systems worldwide. The main purpose of this project is to develop software that can detect and mitigate the ransomware virus. This project helps to secure users’ data from being infected by the ransomware. At the same time, this software also has functionality to mitigate the suspicious process that have been assumed as a ransomware virus.